Lab-on-Chip Microsystems for Ex Vivo Network of Neurons Studies: A Review - Zhang, Hongyong; Rong, Guoguang; Bian, Sumin; Sawan, Mohamad (Frontiers in Bioengineering and Biotechnology, 2022)
Increasing population is suffering from neurological disorders nowadays, with no effective therapy available to treat. Explicit knowledge of network of neurons (NoN) in human brain is the key to understanding the pathology of neurological diseases. Research in NoN developed slower than expected due to the complexity of the human brain and the ethical considerations for in vivo studies. However, advances in nanomaterials and micro/nano-microfabrication have opened up the chances for a deeper understanding of NoN ex vivo, one step closer to in vivo studies. This review, therefore, summarizes the latest advances in lab-on-chips microsystems for ex vivo NoN studies by focusing on the advanced materials, techniques, and models for ex vivo NoN studies. The essential methods to construct lab-on-chip are microfluidics and microelectrode arrays. Through combination with functional biomaterials and biocompatible materials, the microfluidics and microelectrode arrays enable to develop various models for ex vivo NoN studies. This review also includes the state-of-the-art brain slides- and organoids-on-chip models. The end of this review discusses the previous issues and future perspectives for NoN studies.